Faktor-faktor yang Mempengaruhi Personal Hygiene pada Siswa Madrasah Aliyah (MA) Boarding School - Faizah, Atifah Nur; Pertiwi, Wiwik Eko (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2023)
Background. Schools with a dormitory system allow disease transmission and students who live in dormitories are more susceptible to contracting disease. Objective. This research aims to analyze the factors that influence personal hygiene among Madrasah Aliyah (MA) boarding school students in Cilegon City in 2023. Method. The research was conducted in April – June 2023. This research used quantitative descriptive methods. Data analysis uses a cross-sectional approach with bivariate tests. The sample was 170 students taken by simple random sampling. Results. The research results showed mean score of respondents' personal hygiene was 52.7 (scale 100). Environmental hygiene is 68.2% in the good category, boarding school guardians play a role (56.5%) and the exposure to information category is 67.1%. Most of the respondents' parents' jobs include non-formal work with a high educational background. Personal hygiene of boarding school students is influenced by environmental hygiene (pv=0,000), the role of boarding school guardians (pv=0,013), parents' occupation (pv=0,003) and background parental education (pv=0,003). Parents who have high education have a 5 times higher chance of encouraging students' personal hygiene better than parents who have low education. School administrators are expected to increase the role of boarding school guardians in supervising students' personal hygiene.